ANALISIS COULOMB STRESS GEMPA BUMI DELI SERDANG 16 JANUARI 2017 - Setiadi, Tio Azhar Prakoso; Perdana, Yusuf Hadi; Rohadi, Supriyanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Earthquake magnitude M 5,6 shaken around Deli Serdang, North Sumatera on January 16th 2017. This research aims to understand Coloumb stress changes of Deli Serdang Earthquake. The analysis of Coloumb stress changes has done to indicate the influence of mainshock toward aftershocks. Earthquake source mechanisms data obtained from Global Centroid Moment Tensor (GCMT) and German Research Centre for Geosciences (GFZ). The distribution of the mainshock and aftershocks had been relocated using Modified Joint Hypocenter Determination (MJHD) method. We used arrival time of primary and secondary wave phase to relocate the hypocenter. The data obtained from the Indonesian Agency for Meteorology Climatology and Geophysics (BMKG) in the period from January 16th 2017 to January 30th 2017. Keywords: Coloumb stress changes, MJHD relocation, Deli Serdang earthquake